Comprehensive periodontal treatment in generalized stage iv, grade c periodontitis: a clinical case report - Chokami Rafiei, Sahar; Makdisi, Jowel; Mohamad Mirzapour, Samira (Brazilian Dental Science, 2020)
Generalized stage IV, grade C periodontitis results in rapid bone destruction in the periodontium and can lead to early tooth loss. Scaling and root planing (SRP) complemented by systemic antibiotics, access surgery, regenerative techniques and implant placement are among the treatments used for patients with this condition. The aim of this article is to report a comprehensive periodontal treatment in a 23-year-old male who was referred to the periodontology department due to complaints of tooth mobility and gum infections diagnosed with generalized stage IV, grade C periodontitis according to the clinical, systemic, and family history features observed. Thorough non-surgical periodontal treatment consisting of scaling and root planing was provided, followed by a series of regenerative periodontal surgeries including guided tissue regeneration (GTR) and guided bone regeneration(GBR) to manage advanced bone defects. Six months after periodontal therapy, all implants were inserted using a one-stage approach and Six months later, they were restored with porcelain fused to metal crowns. During the one and two-year follow-ups, the teeth and implants did not show any signs of instability, attachment loss or bone loss. This case report shows that within the limitations of this study a successful outcome can be achieved with an early diagnosis and treatment involving elimination of infectious microorganisms and meticulous long-term maintenance combined with regenerative techniques and implant placement to restore the masticatory function and improve the quality of life for the patient. However further investigation and clinical studies are required to confirm these results.KEYWORDSStage IV grade C periodontitis; Aggressive periodontitis; Dental implants; Maintenance; Regeneration.